STRATEGI DINAS PARIWISATA DAN KEBUDAYAAN KOTA BATAM DALAM MENGEMBANGKAN KOTA BATAM SEBAGAI DESTINASI WISATA MICE (MEETING, INTENCIVE, CONFERENCE AND EXHIBITION) TAHUN 2011-2014 - Rizki, Silvia; ", Hasanuddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Batam is one of the cities in Riau Islands province located geographically very close to some of the neighboring countries as a business and services center in the Asia Pacific region provides a huge advantage to attract foreign tourists. This is evidenced by the growing number of foreign tourists coming to Batam every year and with the appointment of Batam as one of the 10 City of by the government as a city of MICE tourism in Indonesia has a big impact (multiplier effect) against those who benefited from the event MICE. MICE tourism is an activity that leads the travel business meetings, negotiations both at national and international scale. This thesis discusses the strategy undertaken by the Department of Tourism and Culture in Batam in developing MICE tourism as a leading tourist impact on increasing revenues and the number of tourists visiting Batam.Based on the results of research conducted there are several factors inhibiting the development of Batam as a destination for MICE tourism is one of them the lack of awareness (consciousness) community of the importance of MICE tourism, the lack of database MICE display needs as well as the level of tourists MICE came to Batam and the lack of quality human resources in MICE certified field service.Keyword: Batam, Strategy Department of Tourism and Culture in Batam, MICE, Multipplier Effect